VDAC2 enables BAX to mediate apoptosis and limit tumor development - Hui San Chin (Nature Portfolio, 2018)
BAX and BAK are pro-apoptotic proteins whose activity is essential for the action of many anti-cancer drugs and to suppress tumorigenesis. Here, the authors perform a genome-wide CRISPR/Cas9 screen and identify VDAC2 as a promoter of BAX-mediated apoptosis that is important for an efficient chemotherapeutic response and to suppress tumor formation.